An analysis and empirical study on the related factors of college oral English teaching reform. (September 2020) - Shi, Moli; Cui, Faqiang
Abstract: In order to effectively improve college students' oral English expression ability, this article uses continuous innovation to improve the evaluation teaching method for the first time, facing 90 first-year students of 2019 university, and has carried out two consecutive semesters of reform. The SPSS software was used to conduct sample t-test on the three oral comprehensive evaluation data before, during and after the reform. It is concluded that the continuous reform of "thinking, practice and innovation" for more than one year can greatly help college students to effectively improve their oral expression ability, but it cannot exceed the correctness of traditional teaching methods in language form. At the end of the article, it is innovative to put forward the simultaneous reform of reading teaching and listening teaching, which can shorten the period of oral teaching reform and accelerate the improvement of comprehensive oral ability.